A software for energy optimisation using pinch analysis - Abdul Manan, Zainuddin; Ooi, Boon Lee (Faculty of Chemical and Natural Resources Engineering, UTM, 2001)
Pinch technology is a well-established procedure for the optimization of heat recovery in chemical process plants. The advent of pinch technology provides a comprehensive as well as systematic approach to maximise a plant's energy efficiency. Based on the 1st law principles, in some cases, the technique is amenable for use with commercial spreadsheets or even with hand calculations. Optimisation of medium and large scale oleochemical as well as petrochemical processes, however, could be significantly expedited through the use of computer software. This paper describes the key features of the first Pinch Analysis software developed locally for energy optimization based on the Pinch Analysis principles. The software allows rapid construction of the composite and grand composite curves and the automatic optimal placements of utilities aimed at maximixing the energy efficiency. An interface for heat exchange network design that includes an entalphy scale is an added advantage as it clearly shows the heat balances of heat-exchanging streams. The feature is missing in other Pinch Analysis software available in the global market.